How and under Which Conditions Can We Best Combine Research on School Effectiveness with Research on School Improvement? Establishing Connections Using the Dynamic Approach to School Improvement - Panayiotis Antoniou; Leonidas Kyriakides; Evi Charalambous (MDPI AG, 2022)
This paper aims to discuss how and under which conditions can we best combine research on School Effectiveness with research on School Improvement by utilizing the Dynamic Approach (DA) to School Improvement. We firstly elaborate on the difficulties that exist in trying to merge results from research on School Effectiveness with research on School Improvement. Then, we discuss the need and potential benefit from merging the two research strands, and finally we propose a fruitful merging with reference to the DA framework. Studies that have utilized the DA are also presented and their implications for research, policy and practice are discussed. The last section summarizes the results of the studies that have utilized the DA to highlight conditions that could facilitate a productive merging of the School Effectiveness and School Improvement research.